Measurements of 12C ions beam fragmentation at large angle with an Emulsion Cloud Chamber. (18th August 2017) - Alexandrov, A.; Lellis, G. De; Crescenzo, A. Di; Lauria, A.; Montesi, M.C.; Pastore, A.; Patera, V.; Sarti, A.; Tioukov, V.
Abstract: Hadron radiotherapy is a powerful technique for the treatment of deep-seated tumours. The physical dose distribution of hadron beams is characterized by a small dose delivered in the entrance channel and a large dose in the Bragg peak area. Fragmentation of the incident particles and struck nuclei occurs along the hadron path. Knowledge of the fragment energies and angular distributions is crucial for the validation of the models used in treatment planning systems. We report on large angle fragmentation measurements of a 400 MeV/n 12 C beam impinging on a composite target at the GSI laboratory in Germany. The detector was made of 300 micron thick nuclear emulsion films, with sub-micrometric spatial resolution and large angle track detection capability, interleaved with passive material. Thanks to newly developed techniques in the automated scanning of emulsions it was possible to extend the angular range of detected particles. This resulted in the first measurement of the angular and momentum spectrum for fragments emitted in the range from 34 ̂ to 81 ̂ .